Inhibition of cell adhesion by anti–P-selectin aptamer: a new potential therapeutic agent for sickle cell disease - Gutsaeva, Diana R. (American Society of Hematology, 2011)
Adhesive interactions between circulating sickle red blood cells (RBCs), leukocytes, and endothelial cells are major pathophysiologic events in sickle cell disease (SCD). To develop new therapeutics that efficiently inhibit adhesive interactions, we generated an anti–P-selectin aptamer and examined its effects on cell adhesion using knockout-transgenic SCD model mice. Aptamers, single-stranded oligonucleotides that bind molecular targets with high affinity and specificity, are emerging as new therapeutics for cardiovascular and hematologic disorders. In vitro studies found that the anti–P-selectin aptamer exhibits high specificity to mouse P-selectin but not other selectins. SCD mice were injected with the anti–P-selectin aptamer, and cell adhesion was observed under hypoxia. The anti–P-selectin aptamer inhibited the adhesion of sickle RBCs and leukocytes to endothelial cells by 90% and 80%, respectively. The anti–P-selectin aptamer also increased microvascular flow velocities and reduced the leukocyte rolling flux. SCD mice treated with the anti–P-selectin aptamer demonstrated a reduced mortality rate associated with the experimental procedures compared with control mice. These results demonstrate that anti–P-selectin aptamer efficiently inhibits the adhesion of both sickle RBCs and leukocytes to endothelial cells in SCD model mice, suggesting a critical role for P-selectin in cell adhesion. Anti–P-selectin aptamer may be useful as a novel therapeutic agent for SCD.